Measurement of Calcium and Vitamin D3 Levels in the Blood Serum of Smokers and Compared to Healthy Controls - Mahmood, Ahmed Thaher; Ahmed, Atheer Shehab; Mohammed, Ahmed Jasim (American Journal of Biology and Natural Sciences, 2024)
This study aims to determine the evolution of calcium and vitamin D3 levels in the blood serum of smokers, and how smoking duration affects each level compared to healthy individuals The study was conducted in the city of Baqubah (at the specialized Al-Shams laboratory), where 40 blood samples were taken – 20 from smokers and 20 from non-smokers in good health aged 20 to 70 years old. The results of the current study showed a significant decrease in the level of probability (P<0.001) in the values of average calcium and vitamin D3 in the blood serum of smokers when compared to healthy non-smokers. The results also indicated that the duration of smoking does not have a significant impact on the levels of calcium and vitamin D3 in the blood serum, although there is an inverse relationship between the duration of smoking and the levels of calcium and vitamin D3, as their levels decreased with the increase in the duration of smoking, but they were not statistically significant. The results of this study show that smoking cigarettes is linked to bad health effects in the body. Also, smoking cigarettes may mess up the gut system’s calcium absorption systems, making it harder for the body to absorb calcium and vitamin D3.